Thermal behavior of residues (sludge) originated from Araraquara water and sewage treatment station - Capana, Alex S. [UNESP]; Martins, Quezia V. [UNESP]; Crespi, Marisa Spirandeli [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Barud, Hernane S. [UNESP] (Springer, 2009)
The number of the cities with canalized water and sewage treatment stations has increased lately and consequently having in mind the great concern on environment preservation and the quality of the water used by society. However, these stations are nowadays causing another kind of problem: a huge quantity of sludge as residue. Due to the implication of the residue on the environment and, consequently, to human life quality, performing of an accurate investigation about the components of such sludge, as well as the thermal stability of this residue in the environment become necessary. This paper presents a study on sludge from water and sewage treatment station, as well as the thermal characterization of residue. Such study was performed through FTIR, atomic absorption, thermoanalytical (TG/DTG, DTA) techniques, that made it possible to observe that the main components of the sludge are clay, carbonates and organic substance, presenting a low rate of metals and a unique thermal behavior since the sludge from the treatment station has a higher thermal stability.
Keywords: Residue; Sludge; Sewage; Thermal stability